Evaluation of the effectiveness of a novel gait trainer in increasing the functionality of individuals with motor impairment: A case series. Issue 2 (15th March 2019) - Raveh, Eitan; Schwartz, Isabella; Karniel, Naama; Portnoy, Sigal
ABSTRACT: Regaining the ability to independently ambulate following a physical disability can increase functional ability and participation of patients in daily life. Gait trainers are assistive devices that enable body support and provide safety during gait. However, most conventional gait trainers are pre-configured to a constant position, therefore not suitable for practicing sit-to-stand function, and require assistance from a caregiver in order to mount the device from a sitting position. We therefore evaluated the effectiveness of a dynamically-adjusting gait trainer, designed to provide independence and safety during gait and various activities, in both lab setting and at home in four subjects (one female, three males, ages 32–79 years) with limited ambulation. Spatiotemporal parameters and gait symmetry were recorded, as well as activity levels, actual use of device, and satisfaction. Although gait parameters and physical activity levels were not notably improved, and in one case were worsened, three subjects reported positive experience with the gait trainer. The new gait trainer may have advantages in supporting users with limited mobility during walking and various functions and decrease the risk for falls. A longer practice time and individual fitting process are recommended for better accommodation to the new possibilities.